The Dynamics of Judicial Administration in the Rule of Law Management System - Marpi, Yapiter (Lembaga Layanan Pendidikan Tinggi Wilayah III DKI Jakarta, 2022)
Indonesian state system has been systematized into Triaspolitika management administratively into a state of law in accordance with the provisions of Article 24 paragraph (2) of the 1945 Constitution of the Indonesia of republic which states that judicial power is exercised by a Supreme Court Body and judicial bodies under it within the general court environment environment of religious court, environment of military court, environment of state administrative court, and by a Constitutional Court. The dynamic tendency of the judicial administration system to have administrative management duties respectively. The aim of the author is to focus more on the judicial administration system which has not yet optimized functional performance. This research uses normative juridical supported by socio-legal legal materials in a literary manner and supported by descriptive analytical. The conclusion of this research is that the results of the analysis of the Administrative Court are deemed necessary for reform, monitoring and evaluation, because it is seen as a court place for cases that are specific itself. With the existence of a court that specifically confidence and confidence in the decisions given in an administrative case and there will be no doubts because, accountable, simple and fulfill the management administration system